We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
+5
815
1
avatar

the recursive rule of sequence is f(n)=f(n-1)-6 if the first term is 20 what is the fourth term of the sequance

 Dec 16, 2015

Best Answer 

 #1
avatar+23278 
+15

the recursive rule of sequence is f(n)=f(n-1)-6 if the first term is 20 what is the fourth term of the sequance

 

\(\begin{array}{rcll} f(n) &=& f(n-1) - 6 \\\\ f(2) &=& f(1) - 6 \qquad f(1) = 20\\ f(2) &=& 20 - 6 \\ f(2) &=& 14 \\\\ f(3) &=& f(2) - 6 \qquad f(2) = 14\\ f(3) &=& 14 - 6 \\ f(3) &=& 8 \\\\ f(4) &=& f(3) - 6 \qquad f(3) = 8\\ f(4) &=& 8 - 6 \\ \mathbf{f(4)} &\mathbf{=}& \mathbf{2} \end{array}\)

 

laugh

 Dec 16, 2015
 #1
avatar+23278 
+15
Best Answer

the recursive rule of sequence is f(n)=f(n-1)-6 if the first term is 20 what is the fourth term of the sequance

 

\(\begin{array}{rcll} f(n) &=& f(n-1) - 6 \\\\ f(2) &=& f(1) - 6 \qquad f(1) = 20\\ f(2) &=& 20 - 6 \\ f(2) &=& 14 \\\\ f(3) &=& f(2) - 6 \qquad f(2) = 14\\ f(3) &=& 14 - 6 \\ f(3) &=& 8 \\\\ f(4) &=& f(3) - 6 \qquad f(3) = 8\\ f(4) &=& 8 - 6 \\ \mathbf{f(4)} &\mathbf{=}& \mathbf{2} \end{array}\)

 

laugh

heureka Dec 16, 2015

29 Online Users